Fe(CN)5@PIL-derived N-doped porous carbon with FeCxNy active sites as a robust electrocatalyst for the oxygen reduction reaction. Issue 1 (19th November 2018) - Zhang, Shao-hua; Gao, Yi-jing; Cheng, Shan; Yan, Yi-long; Zhang, Shi-Jie; Zhuang, Gui-lin; Deng, Sheng-wei; Wei, Zhong-zhe; Zhong, Xing; Wang, Jian-guo
Abstract : FeC x N y /N-PC catalysts derived by Fe(CN)5@PILs show high performance and catalytic activity for the ORR. Abstract : The synthesis and catalytic mechanism of new-type Fe–N co-doping catalysts are important topics for the research on fuel cells. Herein, we report the synthesis and oxygen reduction reaction (ORR) properties of a new Fe–N co-doping carbon composite using poly(ionic liquid)s and ferric salt as precursors. The structural characterizations revealed that the as-prepared material features ordered porous properties with a specific surface area of 719.1 m 2 g −1, corresponding to FeC x N y /N-doped porous carbons (FeC x N y /N-PC). The electrochemical measurements indicated they show superior catalytic activity (Tafel slope of 70.8 mV dec −1 and E 1/2 of 0.84 V), stability and high methanol tolerance compared to the commercial Pt/C catalyst. Furthermore, density functional theory calculations uncovered that the FeC x N y /N-PC composite catalyzes the ORR according to the four-electron associative mechanism with the free-energy barrier of 0.51 eV in the rate-determining formation of H2 O. Interestingly, the electronic structure analysis demonstrated the FeC x N y particles serve as active sites and the synergistic effect of the Fe and N atoms of N-PC can promote the ORR performance.